Genome-wide exploration of metal tolerance protein (MTP) genes in common wheat (Triticum aestivum): insights into metal homeostasis and biofortification - (:unkn) unknown (SPRINGER, 2017)
Metal transport process in plants is a determinant of quality and quantity of the harvest. Although it is among the most important of staple crops, knowledge about genes that encode for membrane-bound metal transporters is scarce in wheat. Metal tolerance proteins (MTPs) are involved in trace metal homeostasis at the sub-cellular level, usually by providing metal efflux out of the cytosol. Here, by using various bioinformatics approaches, genes that encode for MTPs in the hexaploid wheat genome (Triticum aestivum, abbreviated as Ta) were identified and characterized. Based on the comparison with known rice MTPs, the wheat genome contained 20 MTP sequences; named as TaMTP1-8A, B and D. All TaMTPs contained a cation diffusion facilitator (CDF) family domain and most members harbored a zinc transporter dimerization domain. Based on motif, phylogeny and alignment analysis, A, B and D genomes of TaMTP3-7 sequences demonstrated higher homology compared to TaMTP1, 2 and 8. With reference to their rice orthologs, TaMTP1s and TaMTP8s belonged to Zn-CDFs, TaMTP2s to Fe/Zn-CDFs and TaMTP3-7s to Mn-CDFs. Upstream regions of TaMTP genes included diverse cis-regulatory motifs, indicating regulation by developmental stage, tissue type and stresses. A scan of the coding sequences of 20 TaMTPs against published miRNAs predicted a total of 14 potential miRNAs, mainly targeting the members of most diverged groups. Expression analysis showed that several TaMTPs were temporally and spatially regulated during the developmental time-course. In grains, MTPs were preferentially expressed in the aleurone layer, which is known as a reservoir for high concentrations of iron and zinc. The work identified and characterized metal tolerance proteins in common wheat and revealed a potential involvement of MTPs in providing a sink for trace element storage in wheat grains.
Keywords: CDF; Micronutrient; Aleurone; Deficiency; Biofortification; ZINC TRANSPORTER; EXPRESSION ANALYSIS; IRON; ARABIDOPSIS; RICE; MICRORNAS; IDENTIFICATION; ELEMENTS; ACCUMULATION; DEFICIENCY